MULTIPLIKASI EKSPLAN ANTHURIUM (Anthurium sp.) DENGAN PEMBERIAN BENZIL AMINO PURIN (BAP) DAN INDOLE ACETIC ACID (IAA) SECARA KULTUR JARINGAN - Faturrahman Faturrahman (Jurnal Agroteknologi, 2011)
Research has been conducted laboratory Biotechnology Faculty of Agriculture, Islamic University of Riau, Jalan Kaharuddin Nasution Km. 11 Pekanbaru. The purpose of this study was to obtain a combination of BAP and IAA concentrations on multiflikasi anthurium. The design used in this study was completely randomized design (CRD) in factorial which consist of two factors and three replications. The first factor is the provision of BAP, consists of four standards are: B0 (without treatment), B1 (providing 0.1 ppm BAP), B2 (provision of 1 ppm BAP, B3 (gift BAP 10 ppm). While the second factor is the provision of the IAA, consisting of 4 standard also is A0 (without giving IAA), A1 (0.1 ppm of IAA), A2 (IAA giving 10 ppm) and A3 (IAA giving 10 ppm). the parameters observed is the percentage of live eksplant, age appears shoots, roots emerge age, number of shoots, number of roots and shoots high. Observational data were statistically analyzed using BNJ-up and test at the level of 5%. From the results of research in the interaction of BAP and IAA effect on the age emerged shoots, roots emerge age, number of shoots, number of roots and shoots high. BAP singly administration significantly influenced the age emerged shoots, roots appear age, number of shoots, roots and the high number of shoots with no provision of BAP. While a single provision of the IAA significantly affect age emerged shoots, roots emerge age, number of shoots, number of roots and shoots high. To multiflikasi interaction treatment is best in the B1A0 9.33 shoots.